Development of vibration damper to reduce generated stress due to flow induced vibrations in pipeline - Aldausari, Muhammad Kh O; Faris, Waleed Fekry; Ghazaly, Nouby M.; Imihezri, Sharifah (TJPRC Pvt. Ltd., 2020)
The aim of the paper is to investigate the capability of the damper system in limiting the vibration in the pipelines which are specific to the oil and gas industry. Fracture related to pipeline stress is an issue that has impacted many industry quite a lot and the implications have led to huge amounts of times and costs being spent on constantly monitoring and ensuring the lifetime of the pipelines. Most of these pipelines though are very old and cannot be considered to be a part of the new technologies that are in place which means that it becomes crucial for the need for new technologies to tackle the problems related to the system. This paper is an exploration of those issues and tries to make use of dampers and to see the impact on the vibration in the pipelines. The study explores the various other technologies used and recommends future changes that might help in the further reduction of vibration-related stress that is a result of the flow of the liquid in these pipelines. It is found that the vibration dampers have significant effects on reducing the vibration related issue with the help of ANSYS related testing on simple design.